'It's so scary how common this is now:' frames in media coverage of the opioid epidemic by Ohio newspapers and themes in Facebook user reactions. Issue 5 (16th April 2019) - Russell, David; Spence, Naomi J.; Thames, Kelly M.
ABSTRACT: Deaths from opioid overdose in the US have increased five-fold since 1999. Ohio ranks second among states in drug overdose deaths, with more than 39 deaths for every 100, 000 people. In light of this, opioid addiction and related issues have garnered substantial media attention. However, few studies have examined the content and framing of opioid-related media coverage or explored ways that audiences react to coverage of the crisis within their communities. This study attempts to fill this gap through an analysis of opioid-related posts and comments on the public-facing Facebook pages of 42 Ohio newspapers between 2013 and 2017 ( N = 397). Content analysis was used to identify frames in posted newspaper content and themes in comments. Four frames were identified in posted stories: (1) Awareness of the Opioid Epidemic and Affected Populations (34.0% of all posted content; n = 135); (2) Programs, Policies, and Interventions (29.5%; n = 117); (3) Crime, Punishment, Legal Cases, and Law Enforcement (28.2%; n = 112); and (4) Narratives of Addiction and the Long Road to Recovery (8.3%; n = 33). Analyses of Facebook user comments on posted newspaper content revealed five themes: Emotion and Support, Choice and Responsibility, Disease and Treatment, Worthiness, and Attention and Action . Findings indicate both the intensive and diverse efforts of newspapers to cover the epidemic as well as the varied reactions of community members to opioid use and addiction.